Readability of Pre-Tertiary English Course Books in Ghana: Unpacking the Metric-Grader Assessment Interface - Justine Bakuuro; Africanus Diedong; Damasus Tuurosong (Prodi Pendidikan Bahasa Inggris, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Islam Darul Ulum Lamongan*, 2024)
Readability of texts is generally determined by the application of readability metrics. In most cases, the learner (grader) is not directly involved in assessing the readability of texts assigned to his/her grade. This study sought to determine the extent of reconcilability of metric and grader readability assessment values on the same texts. The textual data was culled from the Global Series English textbook series used in Ghanaian Senior High Schools for the teaching of the English language. Applying the mixed methods research, primary data was also collected from a total of 150 graders across the 3 grades of SHS in Ghana. Using a descriptive research design, within the constructivist research paradigm, the study reveals that metric and grader readability assessments do not agree to a very large extent. Only two percent (2%) of the texts were found to be suitable for their intended grades at the senior high school. The grader readability assessment of texts was found to be at variance with the metric readability assessment. Whilst most graders found most texts to be readable (over 96%), metric readability assessment found the same texts to be unreadable (about 98%). Both metric and grader readability assessments need to be conducted on the same texts to conclude properly on their realistic readability status before assigning them to respective grades. This is a result of the wide metric-grader readability assessment disparity. Where the grader readability assessment reveals a text to be readable and the metric readability assessment finds the same text to be unreadable, the grader assessment should be considered as that is a more realistic assessment.